2018
DOI: 10.1038/s41598-018-24381-4
|View full text |Cite
|
Sign up to set email alerts
|

Pineal-dependent increase of hypothalamic neurogenesis contributes to the timing of seasonal reproduction in sheep

Abstract: To survive in temperate latitudes, species rely on the photoperiod to synchronize their physiological functions, including reproduction, with the predictable changes in the environment. In sheep, exposure to decreasing day length reactivates the hypothalamo-pituitary-gonadal axis, while during increasing day length, animals enter a period of sexual rest. Neural stem cells have been detected in the sheep hypothalamus and hypothalamic neurogenesis was found to respond to the photoperiod. However, the physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 72 publications
(86 reference statements)
0
23
0
Order By: Relevance
“…Importantly, a recent study has shown that hypothalamic cell proliferation is dependent on melatonin in sheep. 91 Recent studies suggest other interesting markers, such as Prss56, maybe useful in studying cell proliferation in seasonal animals. 92 Taken together, these data indicate that increased cell proliferation is another common response to short photoperiod in both long-and short-day breeders ( Table 1).…”
Section: Neurog Ene S Is a S A Common Re Sp Onsementioning
confidence: 70%
See 3 more Smart Citations
“…Importantly, a recent study has shown that hypothalamic cell proliferation is dependent on melatonin in sheep. 91 Recent studies suggest other interesting markers, such as Prss56, maybe useful in studying cell proliferation in seasonal animals. 92 Taken together, these data indicate that increased cell proliferation is another common response to short photoperiod in both long-and short-day breeders ( Table 1).…”
Section: Neurog Ene S Is a S A Common Re Sp Onsementioning
confidence: 70%
“…22 also include a previously unrecognised role for inflammatory signals in the healthy brain. Findings in sheep, hamster and F344 rats point to a potential photoperiodic shift in cell proliferation/neurogenesis 50,88,89,91 and this has the potential to explain the striking variation in seasonal phenotype among photoperiodic species. It is proposed that seasonal changes in physiology are related to a changing proportion of specific neurones, which results in a response across the season.…”
Section: Con Cluding Remark Smentioning
confidence: 97%
See 2 more Smart Citations
“…Recent evidence obtained in sheep, using infusion of the anti‐mitotic compound Ara‐C at the bottom of the 3V, hints at a functional role for tanycytic cell proliferation in the timing of the breeding season . How cell proliferation may impact seasonal timing remains unknown .…”
Section: Tanycytes As Stem Cells: Does Hypothalamic Cell Proliferatiomentioning
confidence: 99%